2002
DOI: 10.1111/j.1749-6632.2002.tb02084.x
|View full text |Cite
|
Sign up to set email alerts
|

Aging and the Role of Reactive Nitrogen Species

Abstract: The role of reactive oxygen species and its effects on aging has received considerable attention in the past 47 years since Dr. Denham Harman first proposed the "free radical theory of aging." Though not completely understood due to the incalculable number of pathways involved, the number of manuscripts that facilitate the understanding of the underlying effects of reactive radical species on the oxidative stress on lipids, proteins, and DNA and its contribution to the aging process increases nearly exponentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
115
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(129 citation statements)
references
References 104 publications
6
115
0
4
Order By: Relevance
“…Reactive oxygen species ROS can cause cell and tissue damage and lipid peroxidation, leading to impaired cellular function and alterations in the physico-chemical properties of cell membranes, which in turn disrupt vital functions 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Reactive oxygen species ROS can cause cell and tissue damage and lipid peroxidation, leading to impaired cellular function and alterations in the physico-chemical properties of cell membranes, which in turn disrupt vital functions 14 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Increased levels of nitrotyrosine in a variety of tissues have been identified in over 80 different pathologies, 6 including various neurodegenerative diseases [6][7][8][9] as well as in normal biological aging. [10][11][12][13][14][15] Tyrosine nitration can alter protein structure and function, affect its biological half-life, inactivate enzymes and receptors that depend on tyrosine residues for their activity, and prevent phosphorylation of tyrosine residues important for signal transduction. 15,16 In addition, recent work has shown that tyrosine nitration can have a regulatory role in redox signaling.…”
Section: Introductionmentioning
confidence: 99%
“…3 Accumulation of protein-associated nitrotyrosine has been documented in inflammatory conditions of diverse origin such as atherosclerosis (1), respiratory disease (2), transplant rejection (3), multiple sclerosis (4), Alzheimer's disease (5), celiac disease (6), arthritis (7)(8)(9), ischemia-reperfusion injury (10), autoimmune diabetes (11), autoimmune uveitis (12), and infectious diseases (13). Although the precise molecular mechanism(s) responsible for in vivo formation of nitrotyrosine is still not firmly established, peroxynitrite and other reactive nitrogen species generated during periods of inflammation are thought to be primary intermediates (14,15).…”
mentioning
confidence: 99%